Regional distribution patterns of wetland monocots with different root turnover strategies are associated with local variation in soil temperature. Issue 1 (17th December 2019) - Courchesne, Dominique N.; Wilson, Adrienne Z.; Ryser, Peter
Summary: Herbaceous perennial wetland monocots in Northern Ontario, Canada, show dichotomous root overwintering patterns, either with full senescence in autumn or survival over the winter, comparable to deciduous and evergreen leaf habits in trees. To test if these root strategies differ in their associations with growing season length, soil temperatures were recorded in autumn, winter and spring on 38 wetland sites with their dominant species being either of these two root overwintering strategies, altogether 19 monocot species. Traits associated with these strategies were assessed in garden experiments for a subset of these species. Sites with species with autumn‐senescing roots were, on average, warmer than sites with species with overwintering roots. The 13 coldest sites were all sites of species with overwintering roots. Spring shoot growth in the field was delayed in species with autumn‐senescing roots, despite their higher shoot relative growth rates in the garden, possibly due to the necessity to produce roots first. We conclude that species with autumn‐senescing roots are more constrained by temperature than species with overwintering roots, limiting their occurrence in cool climates to locally warm soils and constraining their distribution towards the north. This is comparable to constraints on distribution of deciduous and evergreen trees.